MAK-Sammlung online - MAK - Österreichisches Museum für Angewandte Kunst / Gegenwartskunst (2010)
[Dt.:] Das MAK - Österreichisches Museum für angewandte Kunst / Gegenwartskunst bietet über diese Website Zugang zu seiner Sammlung. - [Engl.:] The MAK Austrian Museum of Applied Arts / Contemporary Art provides access to its collection via this website. Japanese woodblock prints (Ukiyo-e), east-asian art, late-antique textiles, posters, ornamental prints, drawings of the Wiener Werkstätte, Joseph Binder's graphic design and artist's books can be searched.